2021
DOI: 10.3847/1538-3881/ac20d6
|View full text |Cite
|
Sign up to set email alerts
|

Toward Precise Galaxy Evolution: A Comparison between Spectral Indices of z ∼1 Galaxies in the IllustrisTNG Simulation and the LEGA-C Survey

Abstract: We present the first comparison of observed stellar continuum spectra of high-redshift galaxies and mock galaxy spectra generated from hydrodynamical simulations. The mock spectra are produced from the IllustrisTNG TNG100 simulation combined with stellar population models and take into account dust attenuation and realistic observational effects (aperture effects and noise). We compare the simulated D n 4000 and EW(Hδ) of galaxies with   M M 10.5 log 11.5 * ( ) at 0.6 z 1.0 to the observed distributions from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…Keeping these complexities in mind, from Figure 5 we immediately notice that the observed galaxies occupy wider distributions in age and metallicity, as well as systematically older and more metal-poor populations. Our measurement of overall older populations in 3D-HST than TNG100 is in agreement with the same result for LEGA-C (van der Wel et al 2016, 2021) versus TNG100 galaxies by Wu et al (2021).…”
Section: Dust-free Color Comparisonsupporting
confidence: 91%
“…Keeping these complexities in mind, from Figure 5 we immediately notice that the observed galaxies occupy wider distributions in age and metallicity, as well as systematically older and more metal-poor populations. Our measurement of overall older populations in 3D-HST than TNG100 is in agreement with the same result for LEGA-C (van der Wel et al 2016, 2021) versus TNG100 galaxies by Wu et al (2021).…”
Section: Dust-free Color Comparisonsupporting
confidence: 91%
“…These mechanisms also result in different quenching timescales, with gas removal processes causing rapid suppression of the star formation , while starvation mechanisms -preventing the accretion of fresh gas -require longer quenching timescales (100 Myr -1 Gyr) [19][20][21][22][23], and result in different imprints on the chemical enrichment level of galaxies [24][25][26]. Different models expect these mechanisms to play different roles across the cosmic epochs [11][12][13][27][28][29][30][31][32]. Constraining these models requires the identification and characterisation of quiescent galaxies at large cosmological distances.…”
mentioning
confidence: 99%
“…In Figure 15, we plot our sample as a combined median, where σ is the median of all of the line moment measurements presented in Section 3.2, which is 260 ± 21 km s −1 . As a comparison, measurements of local ETGs that are based on the MASSIVE (Davis et al 2019) and ATLAS 3D (Cappellari et al 2013) surveys are shown, as well as the quiescent galaxies (D n 4000 > 1.55; Kauffmann et al 2003;Wu et al 2018) at z = 0.6-1.0 based on the LEGA-C survey Wu et al 2021) and some compiled z ∼ 2−4 spectroscopically confirmed quiescent galaxies (Stockmann et al 2020;Valentino et al 2020). The results from the similar analyses of mostly fainter SMGs presented by Birkin et al (2021) are also shown.…”
Section: Connecting To the Descendantsmentioning
confidence: 95%
“…Thus, the observed number density of SMGs with S 870 > 12.4 mJy is about 3 × 10 −7 cMpc −3 for all three redshift bins. However, assuming a typical lifetime of 100 Myr for our sample SMGs (C.-L. Liao et al 2022, in preparation), the duty cycle corrected number densities are 3.3 +2.8 −1.8 × 10 −6 , -+ -1.9 10 et al 2019) and ATLAS 3D (Cappellari et al 2013), is plotted in gray, and recent measurements of z = 0.6-1.0 and z ∼ 2−4 quiescent galaxies (QGs) are shown as 2D histogram with green hexagon bins (van der Wu et al 2021) and blue squares (Stockmann et al 2020;Valentino et al 2020), respectively. We also include results of fainter SMGs that also have spectroscopic redshift measurements (Birkin et al 2021).…”
Section: Connecting To the Descendantsmentioning
confidence: 99%